FACTOR ANALYSIS OF LEARNING DIFFICULTIES IN MATHEMATICS FOR GRADE 5 FRACTION CALCULATION MATERIAL - Unaenah, Een; Wulandari, Cahya; Nurzahro, Yufaida; Aulya, Zahra (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2022)
This study aims to describe the difficulties in learning mathematical fraction calculations in Grade 5 at SD Poris Gaga 8. The research method employed is qualitative, specifically a case study involving students and teachers of Grade 5 at SD. Data collection is carried out through observation techniques and face-to-face interviews. The study's results on factors contributing to students' difficulties in learning material about fractions include both students' cognitive aspects and physical aspects related to fractions. The challenges in learning, considering the students' cognitive conditions, are influenced by their concentration levels during math lessons. This is often attributed to students' disinterest in studying mathematics, their tendency to become easily bored at school, and an unfavorable learning environment. Regarding the material aspects of learning fractional calculations, students face difficulties due to their lack of familiarity with common denominators, general understanding of denominators, and the fundamental concepts of multiplying and dividing fractions. Furthermore, when solving problems involving fraction division, students struggle to effectively model these problems using appropriate mathematical approaches.